The Impact of the Tropical Water Project on Darbandikhan Dam and Diyala River Basin - ., Dana Muhammad Faraj; ., Kawa Zaidan (Iraqi Journal of Civil Engineering, 2022)
Iran has recently started a well-planned project, called Tropical Water Project (TWP), to build more dams, tunnels, and canals on the main tributaries of the Diyala River (Sirwan and Zmkan) to irrigate agricultural areas inside and outside the Diyala River basin. One task in the TWP project is diverting a large volume of the water flowing through the Sirwan and Zmkan rivers through a series of tunnels. The largest one, called Nowsud water conveyance tunnel, transports water from Hirwa dam to Azgala dam to irrigate millions of hectares of new agricultural areas extending from Kermanshah province in the AL Ahwaz province. This research aims to identify the different features and the size of this project as well as the extent of its impact on the Diyala River and Darbandikhan dam. From the results, it was found that the TWP project consists of 14 dams constructed on Sirwan and Zmkan rivers and their tributaries with a total storage capacity of 1.9 Milliard cubic meters and of about 150 km long tunnels to divert more than one Milliard m3 of water to another basin. In addition, it has been found that after the full operation of the TWP project, the catchment area of Darbandikhan dam will lose 77% of its original one.